Cyotkines as Potential Therapies for Human Immunodeficiency Virus Infections - Robert W Sidwell; John D Morrey; Reed P Warren (Canadian Journal of Infectious Diseases)
Cytokines are attracting increased interest as potential therapies for human immunodeficiency virus (HIV) infections. This attraction has particularly arisen as these cytokines have become more commercially available through recombinant technologies. This review focuses on the effects of these biological response modifiers on preclinical HIV and related retrovirus infections. Cytokines that have particularly been considered for HIV disease control include: interferons -α , -β and -γ, interleukins-2. -3. -4. -6 and -7; tumour necrosis factors -α and -β; and the colony stimulating factors. Efficacy has especially been seen when these cytokines have been used in combination with the more conventional antiviral agents. Due to the many biological functions exerted by cytokines and their interweaving of biological effects with other cytokines, they appear to have the potential to both inhibit as well as enhance viral infections, depending upon how they are used, and caution is therefore urged in their use.